(untitled) (The Pakistan Development Review, 1990)
The use and adoption of indivisible techndogy are not restricted by ownership or class structure. We have found, however, that in 1972,-and still in 1980, though tubewells were owned by a minor fraction of total farm househdds (and predominan tly by the large and medium farmers), they were used by a substan tial proportion of farm households. Predictably, .the user-owner ratio was the highest in the case of the small farmers in all provinces. The relative importance of the small and medium farmers as owners of this techndogy increased over the period, particularly in the Punjab where tubewells are concen trated. The development of a hire market in tube well services has ven birth to a new entrepreneurial class in the rural areas. Inequalities in rural income are dwindling and benefits emanating from ntechnology are shared. These conclusions are of vital importance because they negate the existing views and show that (i) the indivisibility of technology has not been a barrier to its adoption, and that (ii) the fact that the share of the small and medium farmers in the ownership of tubewells has increased gives support to the thesis that if a technology is profi table, farmers will adopt it where possible. Thus, the view that small farmers are conserva tive and resist change can no longer be sustained Further, it shows that the small and medium farm sector, in particular, holds the potential for investment in techndogy.